Effects of Seasonal Transitions on Population Dynamics of Fruit Flies in Capsicum annuum and Solanum lycopersicum in Batu City, Indonesia - Agustina, Dwi Kameluh; Leksono, Amin Setyo; Yanuwiadi, Bagyo; Rizali, Akhmad; Abdullah, Saiful Arif; Abdullah, Muhammad (Universitas Negeri Semarang, 2025)
Fruit flies remain a persistent threat to horticultural production, especially in tropical regions where seasonal shifts can significantly affect their population dynamics. This study investigated the species composition, diversity, and environmental drivers of fruit fly populations infesting Capsicum annuum and Solanum lycopersicum over a one-year period in Batu City, Indonesia. Using weekly sampling across four seasonal phases—dry-to-rainy transition, rainy season, rainy-to-dry transition, and dry season—fruit fly specimens were collected, reared, and identified. Environmental variables, including temperature, humidity, rainfall, light intensity, and pesticide application frequency, were monitored and analyzed in relation to fruit fly abundance using Principal Component Analysis (PCA) and multiple linear regression. A total of four species were recorded: Bactrocera carambolae, Bactrocera dorsalis, Atherigona sp, and Silba sp, with the latter representing a new regional record for East Java. Population peaks occurred during the rainy season and its transitional periods, while significant declines were observed during the dry months. Regression models revealed that temperature and humidity supported population growth, whereas pesticide use had a consistently suppressive effect—particularly for B. dorsalis and Atherigona sp. However, the models explained only 20–50% of the variation, suggesting that additional ecological factors may be at play. These findings deepen our understanding of fruit fly ecology in tropical systems and highlight the importance of integrating climatic and agronomic data in pest management strategies. The discovery of Silba sp. further enriches current biogeographical knowledge and signals the need for adaptive, interdisciplinary approaches to sustainable pest control.